2015
DOI: 10.1097/brs.0000000000000599
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Day Perioperative Outcomes in Spinal Fusion by Specialty Within the NSQIP Database

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 11 publications
1
69
2
Order By: Relevance
“…Moreover, this rate is clearly lower than what has previously been reported for fusion procedures [20,26]. Interestingly, the rate of unintentional durotomies was very low and there were no major complications such as nerve injury, DVT, PE, and deep-wound infections [9,16,24,27].…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, this rate is clearly lower than what has previously been reported for fusion procedures [20,26]. Interestingly, the rate of unintentional durotomies was very low and there were no major complications such as nerve injury, DVT, PE, and deep-wound infections [9,16,24,27].…”
Section: Discussionmentioning
confidence: 67%
“…56 This data source has been previously used to evaluate patients undergoing neurosurgical intervention, 7,9,11,13,24,28,33,[47][48][49]52,53 including craniotomy for tumor. [1][2][3]10,14,29,54 The NSQIP database has been exempted as not human subject research by our institutional review board.…”
Section: Data Sourcementioning
confidence: 99%
“…The accuracy of data collection by the NSQIP (including cumulative incidence and reasons for readmission) has been externally validated, 84 and this data source has been previously used to evaluate patients undergoing neurosurgical intervention, 4,8,12,14,15,28,29,45,54,83 including spine surgery. 2,6,9,10,25,40,53,59,61,82,91 Our institutional review board has exempted the de-identified NSQIP data set from individual review.…”
Section: Data Sourcementioning
confidence: 99%
“…3,7,9,49,59,60,61,71,77,90,91 Despite its utility in evaluating perioperative complications and adverse outcomes, few studies have used the NSQIP to analyze the outcomes of patients undergoing surgery for spinal tumors. The goal of this study was to evaluate the 30-day cumulative incidence, time to event, and predictors of major complications, unplanned reoperations, and readmissions after surgery for primary and secondary spinal tumors.…”
mentioning
confidence: 99%